A SaaS Development Platform based on Cloud Computing - Qingpeng ZENG; Shuixiu WU (Institute of Advanced Engineering and Science, 2013)
Using Java technology to research and develop a SaaS development and maintenance platform which is based on cloud computing ,it includes many modules such as the cloud computing load network, application server, development framework, cloud computing development engine , operation and maintenance system and so on. the platform can provide a complete network client software development scheme for the development of software and integration, it can reduce the user’s request to SaaS technology, and it can help the user to achieve operation service of product on the Internet. at the same time, the platform as a development tool can be used as a powerful supplement of core electronic devices, high-end general chip and basic software products. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2320